Validity of Sluggish Cognitive Tempo in South America: An Initial Examination Using Mother and Teacher Ratings of Chilean Children - Belmar, Marta (J Atten Disord, 2015)
OBJECTIVE. Our objective was to examine the validity of sluggish cognitive tempo (SCT) and attention-deficit/hyperactivity disorder (ADHD) inattention (IN) symptoms in children from Chile. METHOD. Mothers and teachers rated SCT, ADHD-IN, ADHD-hyperactivity/impulsivity (HI), oppositional defiant disorder (ODD), anxiety, depression, academic impairment, social impairment, and peer rejection (teachers only) in 652 Chilean children (55% boys) ages 6–14. RESULTS. For both mother and teacher ratings, the eight SCT symptoms and nine ADHD-IN symptoms showed substantial loadings on their respective factors (convergent validity) along with loadings close to zero on the alternative factor (discriminant validity). ADHD-IN showed a uniquely stronger relationship than SCT with ADHD-HI and ODD whereas SCT showed a uniquely stronger relationship than ADHD-IN with anxiety and depression. Although ADHD-IN uniquely predicted academic impairment and social difficulties, SCT did not. CONCLUSIONS. This study provides the first evidence for the validity of SCT among children outside of North America or Western Europe.